Joy in the Dirt: Discovering Indenture's Wild Places - Naidoo, Pralini (Art/Research International, 2022)
I was born in South Africa, as were my parents and grandparents. We have descended from people who had been brought to South Africa through indenture, a colonial labour system that introduced alien agricultural methods and an alien workforce from India, to optimise monocultures like sugarcane. My very presence here is, therefore, entangled with colonialism’s domestication and mastery over land, plant, and people (Indigenous and indentured). I have never felt alien here. Why was that? What about the indenture stories of people, land and plant, beyond empire’s mastery and control—my ancestral wild places? And was there room within these wild places to heal colonial wounds across our ethnic and racial barriers? What was lost? Could my PhD2 research transcripts address some of those losses? This paper contains poems that emerged from PhD research interviews, my fieldnotes, my father's memoirs, and letters from my ancestral archives. A poetic lens gave me a decolonial language to inspect the archives and transcripts with some of these questions in mind.